Multielemental single–atom-thick A layers in nanolaminated V(2)(Sn, A) C (A = Fe, Co, Ni, Mn) for tailoring magnetic properties - Li, Youbing (Proc Natl Acad Sci U S A, 2020)
Tailoring of individual single–atom-thick layers in nanolaminated materials offers atomic-level control over material properties. Nonetheless, multielement alloying in individual atomic layers in nanolaminates is largely unexplored. Here, we report 15 inherently nanolaminated V(2)(A(x)Sn(1-x))C (A = Fe, Co, Ni, Mn, and combinations thereof, with x ∼ 1/3) MAX phases synthesized by an alloy-guided reaction. The simultaneous occupancy of the 4 magnetic elements and Sn in the individual single–atom-thick A layers constitutes high-entropy MAX phase in which multielemental alloying exclusively occurs in the 2-dimensional (2D) A layers. V(2)(A(x)Sn(1-x))C exhibit distinct ferromagnetic behavior that can be compositionally tailored from the multielement A-layer alloying. Density functional theory and phase diagram calculations are performed to understand the structure stability of these MAX phases. This 2D multielemental alloying approach provides a structural design route to discover nanolaminated materials and expand their chemical and physical properties. In fact, the magnetic behavior of these multielemental MAX phases shows strong dependency on the combination of various elements.